Characteristics and prognostic factors of very elderly patients admitted to the intensive care unit - Song-I Lee; Younsuck Koh; Jin Won Huh; Sang-Bum Hong; Chae-Man Lim (Acute and Critical Care, 2022)
Background Korea is rapidly becoming a super aging society and is facing the increased burden of critical care for the elderly people. Traditionally, far-advanced age has been regarded as a triage criterion for intensive care unit (ICU) admission. We evaluated how the characteristics and prognostic factors of very elderly patients (≥85 years) admitted to the ICU changed over the last decade. Methods We retrospectively evaluated the data of patients admitted to the ICU over 11 years (2007–2017). The clinical characteristics and outcomes of the very elderly-patients group were evaluated. Factors associated with mortality were assessed by a cox regression analysis. Results Comparing the first half (2007–2012) and the second half (2013–2017) of the study period, the proportion of very elderly group increased from 603/47,657 (1.3%), to 697/37,756 (1.8%) (P<0.001). Among 1,294 very elderly patients, 1,274 patients were analyzed excluding hopeless discharge (n=20). The non-surgical reasons for ICU admission (67.0% vs. 76.1%, P<0.001) and the percentage of patients with co-morbidities (78.3% vs. 82.7%, P=0.048) were increased. Nevertheless, the hospital mortality decreased (21.3% vs. 14.9%, P=0.001). High creatinine levels, use of vasopressors and ventilator weaning failure were associated with in-hospital mortality. Conclusions The proportion of very elderly people in the ICU increased over the last decade. The non-surgical causes of ICU admission increased compared with the surgical causes. Despite an increasement in ICU admissions of very elderly patients, in-hospital mortality of very elderly ICU patients decreased.